Living Hadith Study: The Shalawat Dalail Al Khairat Tradition in Jorong Gantiang Koto Tuo - Alifah, Nurul; Febriyeni, Febriyeni (International Journal of Research, 2024)
The aim of this research is to find out the hadiths that form the basis, procession and meaning in reading the Dalail Al Khairat prayers in Jorong Gantiang Koto Tuo, Canduang District, Agam Regency. The research method used is qualitative with a phenomenological approach. With Angku Imam's research subject named Mr. Ramzi and the congregation carrying out the tradition of reading the Dalail Al Khairat prayers. The data collection techniques used in this research were observation, interviews and documentation. The results of the research found that the procession of reciting the Dalail Al Khairat prayers in Jorong Gantiang Koto Tuo, Canduang District, Agam Regency began with performing the Maghrib prayer in congregation, then the congregation performed the Sunnah Ba'diyah Maghrib prayer. After that, we continue with reading the shalawat which begins with reading istighfar, the Prophet's shalawat, surah Al-Fatihah, Ayat Kursi and continues with reading the shalawat and prayers in the book Dalail Al Khairat as the wird. Furthermore, the Dalail Al Khairat prayer tradition in Jorong Gantiang Koto Tuo, Canduang District, Agam Regency uses the basis of the hadiths written in the Darratun Nasihin book and the Dalail Al Khairat prayer book. The tradition of praying for Dalail Al Khaira in Jorong Gantiang Koto Tuo, Canduang District, Agam Regency, gives an idea to the community that increasing prayers for the Prophet PBUH can bring many benefits in everyday life